Social Habits (concept, origins, functions) - العقيبة, هند; قرطالي, هلا (Latakia University Journal - Arts and Humanities Sciences Series, 2021)
In our research, we reviewed the concept of social customs through a set of linguistic, methodological and scientific approaches. We have also addressed some of the opinions of scholars and researchers regarding its history of origin and classifications. We uncovered the most important functions that customs achieve in the societies in which they are practiced, which are manifested in the controlling, educational, predictive, economic, and aesthetic function. We used the descriptive and analytical approach to describe this phenomenon, which is one of the most important phenomena in all our societies, in order to present some proposals that would preserve it from extinction and loss.